Motion control of pneumatic muscle actuator: experimental setup and modeling - Sakthivelu, Vasanthan; Chong, Shin Horng (2013)
This paper discusses experimental setup (mechanical testing) & modelling result of pneumatic muscle actuator. In recent times, the Pneumatic Muscle Actuator (PMA) has achieved popularity in the field of research, robotics and industrial application due to its advantages such as light weight actuator, dynamic, powerful and resistant to dust and clean. Due to its nonlinear dynamics, the muscle actuator is difficult to be controlled. In this paper a pneumatic muscle actuator system is developed for motion control purpose. The dynamic system modeling is discussed. Open loop test and static load experiment have been conducted and validated with mathematical model. Finally, a brief conclusion of the pneumatic muscle actuator experimental setup and dynamic system modeling is made.